UMP library Wi-Fi access control system (ULWACS) - Flamino Doril, Zepher (2012)
The wireless technology was introduced to replace the wired connection and itis widely used in today’s work andindustry segment.Nowadays in wirelesstechnology,user from outside are allowed to access the internet a private network in awireless network area as they are not authenticated.This UMP LibraryWi-Fi Access Control System (ULWACS) is develop to program the authentication system and usage-based system that include program for registering and activating user, detect for overdue day and log off the connection between users and access point.The method for implement hotspot is Software Prototyping that includes execution and testing for each step.A study has been conducted on types of access points, IP address and architecture that are suitable for ULWACS implementation. In order to make the development of system completed, the research and methodology has been prepared in term of data collected, software and hardware requirements needed.For the system architecture, it consists of user,access point,and access server only.The design is develop and construct the coding of the program and testing with the access point whether it is successful authorization or not when the system is completed.The success of implementation and development of this project is expected to increase the security in wireless network by requiring the user to register with administration and pay some feebased on time using the hotspot to access internet.